Medicare program; hospital inpatient prospective payment systems for acute care hospitals and the long-term care hospital prospective payment system and fiscal year 2015 rates; quality reporting requirements for specific providers; reasonable compensation equivalents for physician services in excluded hospitals and certain teaching hospitals; provider administrative appeals and judicial review; enforcement provisions for organ transplant centers; and electronic health record (EHR) incentive prog (Federal register, 2014)
We are revising the Medicare hospital inpatient prospective payment systems (IPPS) for operating and capital-related costs of acute care hospitals to implement changes arising from our continuing experience with these systems. Some of these changes implement certain statutory provisions contained in the Patient Protection and Affordable Care Act and the Health Care and Education Reconciliation Act of 2010 (collectively known as the Affordable Care Act), the Protecting Access to Medicare Act of 2014, and other legislation. These changes are applicable to discharges occurring on or after October 1, 2014, unless otherwise specified in this final rule. We also are updating the rate-of-increase limits for certain hospitals excluded from the IPPS that are paid on a reasonable cost basis subject to these limits. The updated rate-of-increase limits are effective for cost reporting periods beginning on or after October 1, 2014. We also are updating the payment policies and the annual payment rates for the Medicare prospective payment system (PPS) for inpatient hospital services provided by long-term care hospitals (LTCHs) and implementing certain statutory changes to the LTCH PPS under the Affordable Care Act and the Pathway for Sustainable Growth Rate (SGR) Reform Act of 2013 and the Protecting Access to Medicare Act of 2014. In addition, we discuss our proposals on the interruption of stay policy for LTCHs and on retiring the "5 percent" payment adjustment for collocated LTCHs. While many of the statutory mandates of the Pathway for SGR Reform Act apply to discharges occurring on or after October 1, 2014, others will not begin to apply until 2016 and beyond. In addition, we are making a number of changes relating to direct graduate medical education (GME) and indirect medical education (IME) payments. We are establishing new requirements or revising requirements for quality reporting by specific providers (acute care hospitals, PPS-exempt cancer hospitals, and LTCHs) that are participating in Medicare. We are updating policies relating to the Hospital Value-Based Purchasing (VBP) Program, the Hospital Readmissions Reduction Program, and the Hospital-Acquired Condition (HAC) Reduction Program. In addition, we are making technical corrections to the regulations governing provider administrative appeals and judicial review; updating the reasonable compensation equivalent (RCE) limits, and revising the methodology for determining such limits, for services furnished by physicians to certain teaching hospitals and hospitals excluded from the IPPS; making regulatory revisions to broaden the specified uses of Medicare Advantage (MA) risk adjustment data and to specify the conditions for release of such risk adjustment data to entities outside of CMS; and making changes to the enforcement procedures for organ transplant centers. We are aligning the reporting and submission timelines for clinical quality measures for the Medicare HER Incentive Program for eligible hospitals and critical access hospitals (CAHs) with the reporting and submission timelines for the Hospital IQR Program. In addition, we provide guidance and clarification of certain policies for eligible hospitals and CAHs such as our policy for reporting zero denominators on clinical quality measures and our policy for case threshold exemptions. In this document, we are finalizing two interim final rules with comment period relating to criteria for disproportionate share hospital uncompensated care payments and extensions of temporary changes to the payment adjustment for low-volume hospitals and of the Medicare-Dependent, Small Rural Hospital (MDH) Program.